2019
DOI: 10.1155/2019/1714608
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Analysis of the Effect of Microscale Components Interaction on Measurements of Fiber Optic Strain Sensors Used in Composite Structures

Abstract: The paper investigates the influence of structural components of a composite material on the strain values measured by using an embedded optical fiber with Bragg gratings. The effect of composite plies and intermediate epoxy layers on the transfer of deformations from the measured object to the optical fiber was studied taking into account various methods of the fiber attachment and surrounding media configurations. A numerical estimation of the effect of the longitudinal and transverse components of the strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Wood et al (2000) have shown very good agreement between strain gauge and embedded FBG for unidirectional composite laminates except for high load values, which they have assumed to be due to compression of grips applied on specimen and fiber. Numerical and experimental approach was used in (Tashkinov and Shardakov, 2019) to show that the FBG measurements can be influenced by surrounding medium. Other than contact-based methods, non-contact devices of strain measurement have been used in recent years since they do not interfere in mechanical response of material.…”
Section: Introductionmentioning
confidence: 99%
“…Wood et al (2000) have shown very good agreement between strain gauge and embedded FBG for unidirectional composite laminates except for high load values, which they have assumed to be due to compression of grips applied on specimen and fiber. Numerical and experimental approach was used in (Tashkinov and Shardakov, 2019) to show that the FBG measurements can be influenced by surrounding medium. Other than contact-based methods, non-contact devices of strain measurement have been used in recent years since they do not interfere in mechanical response of material.…”
Section: Introductionmentioning
confidence: 99%